2010
DOI: 10.1128/mmbr.00033-10
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Fixation and Hydrogen Metabolism in Cyanobacteria

Abstract: SUMMARY This review summarizes recent aspects of (di)nitrogen fixation and (di)hydrogen metabolism, with emphasis on cyanobacteria. These organisms possess several types of the enzyme complexes catalyzing N2 fixation and/or H2 formation or oxidation, namely, two Mo nitrogenases, a V nitrogenase, and two hydrogenases. The two cyanobacterial Ni hydrogenases are differentiated as either uptake or bidirectional hydrogenases. The different forms of both the nitrogenases and hydrogenases are encode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
228
2
7

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 365 publications
(239 citation statements)
references
References 241 publications
(266 reference statements)
2
228
2
7
Order By: Relevance
“…This reaction is catalysed by [FeFe]-H 2 ase, which is extremely sensitive to oxygen and does not require any extra energy in the form of ATP 10 . In the meantime, cyanobacteria may produce hydrogen either as a byproduct of nitrogen fixation using nitrogenase 11 or by a reversible NAD(P)H-dependent NiFe-H 2 ase 12 .…”
mentioning
confidence: 99%
“…This reaction is catalysed by [FeFe]-H 2 ase, which is extremely sensitive to oxygen and does not require any extra energy in the form of ATP 10 . In the meantime, cyanobacteria may produce hydrogen either as a byproduct of nitrogen fixation using nitrogenase 11 or by a reversible NAD(P)H-dependent NiFe-H 2 ase 12 .…”
mentioning
confidence: 99%
“…Photobiological production of H 2 by cyanobacteria and eukaryotic microalgae that use H 2 O as the electron donor has the potential to produce renewable clean energy on a scale sufficient to meet much of the world energy demand (Ghirardi et al 2007(Ghirardi et al , 2009Sakurai and Masukawa 2007;Tamagnini et al 2007;Bothe et al 2010;Ghirardi and Mohanty 2010). In cyanobacteria, H 2 gas is generated by either hydrogenase or nitrogenase (Tamagnini et al 2002(Tamagnini et al , 2007.…”
Section: Introductionmentioning
confidence: 99%
“…In an extensive review article Bothe et al (2010b) have reported more recent information on the mechanisms of N 2 fixation and H 2 metabolism in cyanobacteria including their genetic regulation. According to this article the pattern of pyruvate degradation, ammonium and H 2 formation by nitrogenase, and H 2 uptake by hydrogenases is not only typical of strict and facultative anaerobic bacteria, but also proceeds in cyanobacteria.…”
Section: Journal Of the National Science Foundation Of Sri Lanka 44(2)mentioning
confidence: 99%
“…This cluster accepts reducing equivalents from the electron carriers and also binds MgATP/MgADP. The overall reaction of the reduction of one molecule of nitrogen to produce two molecules of ammonia can be depicted by the following equation from Bothe et al (2010b). …”
Section: Journal Of the National Science Foundation Of Sri Lanka 44(2)mentioning
confidence: 99%
See 1 more Smart Citation